Vulnerability And Government Response To Human Trafficking in Batam During The Pandemic - Lubna Salsabila; Muhammad Badrudin; Karol Teovani Lodan; Timbul Dompak (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
This study aims at understanding how the municipal government of Batam addresses human trafficking and its issues during the COVID-19 pandemic. This research utilizes a qualitative methodology and a descriptive approach to examine how local governments are responding to the mounting number of human trafficking cases, especially those that involve women and children. The Riau Islands Regional Police statistics indicates that there were seven suspects in the TIP case in 2017, seventeen suspects in 2018, six suspects in 2019, and eighteen suspects in 2020. Comparatively, based on the number of cases, there were four cases in 2017, twelve cases in 2018, four cases in 2019, and ten cases in 2020. That which occurs continuously till the lockwodn. The results of the study indicate that: (a) The economic downturn, lack of education, lack of information, and socio-cultural conditions are factors that influence the increase in human trafficking during the pandemic; (b) Weak law enforcement and (c) a lack of cross-sectoral cooperation are the most significant factors that contribute to the escalation of human trafficking in Batam.